Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53797
|View full text |Cite
|
Sign up to set email alerts
|

Making Use of Labyrinth Interaction Flow

Abstract: It is the aim of this publication to attract the designers attention to the end wall flow interactions of shrouded high pressure turbines. One of the key issue for designing better turbines is the understanding of the flow interactions set up by the presence of labyrinth seals. Those interaction flows are carefully examined in this publication using the control volume analysis and the radial equilibrium of forces acting on streamlines. The consequences on secondary flow development and mixing losses are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The geometry configuration of CYLI_A shows a quite different blockage and flow path near the hub due to the sharp edge cut between the cavity itself and the main passage. Here the flow picture in the cavity resemble very closely what reported by Pfau et al [7] for a similar geometry, as shown comparing the right sketch included in Fig. 9.…”
Section: Stage With Cylindrical Blade Technologysupporting
confidence: 84%
See 1 more Smart Citation
“…The geometry configuration of CYLI_A shows a quite different blockage and flow path near the hub due to the sharp edge cut between the cavity itself and the main passage. Here the flow picture in the cavity resemble very closely what reported by Pfau et al [7] for a similar geometry, as shown comparing the right sketch included in Fig. 9.…”
Section: Stage With Cylindrical Blade Technologysupporting
confidence: 84%
“…They underlined the importance of considering unsteady measurement and simulations to obtain a more realistic representation of these effects. Pfau et al [7] concentrated their attention on the steady and unsteady flow interactions within large endwall cavities. They classified open cavities in a systematic way and proposed design modifications in order to make use of the labyrinth interaction flows to improve the overall performance of low aspect ratio shrouded turbines.…”
Section: Introductionmentioning
confidence: 99%
“…This causes flow separation at the stator blades and a highly unsteady flow field at the second stator exit. It should be noted that, about the subject of shroud cavity interactions in shrouded turbines, it was addressed the first time by Denton and Johnson [19]; however, it is only in recent years that this subject has become the focus of much researches [20].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [8] researched the influence of blade tip seal structure on the status of leakage vortex motion in the inlet cavity and outlet cavity of seal by the perspective way. Pfau et al [9] carried out the experimental Corresponding author; E-mail:clh320@126.com analysis on the interaction between the leakage flow and main flow in the passage of two-stage turbine, and attempted to look for the approaches reducing leakage losses and mixing losses. Gao et al [10] studied the influence of tip leakage flow on main flow, and suggested that the ring vortex in the honeycomb seal can significantly reduce the circumferential speed of leakage flow in the seal cavity, so the mixing losses is reduced.…”
Section: Introductionmentioning
confidence: 99%